Inequalities in local government expenditure on environmental and regulatory services in England from 2009 to 2020: a longitudinal ecological study - Ben Barr; Mark Alan Green; Helen E Clough; Xingna Zhang; Katie Fahy; Iain Edward Buchan; Lauren Murrell; Roger Gibb; Marie Anne Chattaway (BMJ Public Health)
Background Gastrointestinal (GI) infections affect one in five people in the UK and local authorities play a crucial role in controlling these infections. However, there have been substantial reductions in funding for environmental and regulatory (ER) services that enable GI infectious disease prevention and control via food safety and infection control (FSIC) services. This study investigates how local funding cuts to these services have varied across England to understand the potential consequences of inequalities in GI infections.Methods We carried out a longitudinal observational ecological study, using a panel of annual data between 2009/2010 and 2020/2021. Analysis of ER service expenditure and FSIC service expenditure included 312 and 303 local authorities respectively. Generalised estimating equation models were used to estimate the annual per cent change of ER service expenditure between 2009/2010 and 2020/2021 in addition to FSIC expenditure change overall, and as a share of total ER expenditure. Models analysed trends by local authority structure, population density and deprivation level.Results ER services saw the largest cuts in unitary authorities, declining by 1.9%. London boroughs had the greatest reductions in FSIC expenditure, decreasing by 9.9%. Both ER and FSIC expenditure decreased with increasing population density. Areas of higher deprivation had the largest reduction in expenditure, with ER and FSIC cuts of 2.4% and 22.8%, respectively, compared with a 1.2% and 7.5% reduction in the least deprived areas. The share of ER expenditure spent on FSIC decreased by 13.4% in the most deprived authorities compared with 6.3% in the least deprived areas.Conclusion The unequal distribution of cuts shows the need for increased and equitable investment into these services to enable resilience to emerging infectious disease threats and to prevent the widening of health inequalities.